Effect of Bubble Size on Electrochemical Reduction of Carbon dioxide to Formic Acid. Issue 1 (April 2021) - Widiatmoko, Pramujo; Hendra Saputera, Wibawa; Devianto, Hary; Nurdin, Isdiriayani; Rivana, Esperanza; Angkasa, Albert
Abstract: A variety of technologies to diminish greenhouse gases CO2 emission have been extensively explored in recent years. One promising technology called electrochemical reduction of CO2 have been developed to convert CO2 into value-added chemicals, such as methanol, ethanol, ethylene, and formic acid. One of important parameter that need to be considered is the size of CO2 bubbles. In general, decreasing bubbles size can increase retention time of carbon dioxide in an electrolyte. In this research, effect of the microbubble size on the effectiveness of electrochemical reduction of carbon dioxide to formic acid was studied. Bubbles with average diameter 0.321 and 0.952 mm were generated through perforated glass apparatus. The FTIR analysis showed peak at 1634 cm −1 which attributed to C=O bonding of formic acid. Smaller bubble size showed relatively more stable and higher electric current during electrolysis, indicating better retention time of carbon dioxide in the electrolyte.